fintech Pembinaan Penggunaan Fintech dan Manajemen Pemasaran Pada Usaha Syifa Parfum : Fintech dan Manajemen Pemasaran - Khadijah, Khadijah (Ikatan Cendekiawan Muda Akuntansi, 2023)
The importance of using fintech is so that businesses know and manage business finances that are being run digitally and can set strategies to use to attract customers to buy the products being sold. Thus, in order to improve the business economy, it is also necessary to think about looking for new opportunities that can be relied upon to increase financial resources. During the visit a discussion with the owner of the Syifa Perfume business regarding the schedule and the right time for implementing the training, then providing material on preparing simple financial reports and marketing management for businesses, and discussions and questions and answers. The training method used is to provide training on good marketing strategy management and to guide Syifa UKM with training methods, lecture lectures, and discussions.